2013
DOI: 10.1530/rep-12-0151
|View full text |Cite|
|
Sign up to set email alerts
|

Sex selection of sperm in farm animals: status report and developmental prospects

Abstract: Pre-selection of spermatozoa based on the relative DNA difference between X-and Y-chromosome bearing populations by flow cytometry is an established method that has been introduced into commercial cattle production. Although several important improvements have increased the sort efficiency, the fertilising ability of sexed spermatozoa based on offspring per insemination is still behind farmers' expectations. The main stress factors, especially on mitochondria, that reduce the lifespan of spermatozoa are descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 149 publications
(151 reference statements)
0
42
0
4
Order By: Relevance
“…Although currently available, commercial sexed semen is not yet an ideal product, but improvements will continue to be made (Seidel, 2012;Rath et al, 2013). While I have emphasized how sexed semen is produced and used in the United States, the situation is very similar in Canada and several other countries.…”
Section: Sexed Semen 163mentioning
confidence: 99%
See 2 more Smart Citations
“…Although currently available, commercial sexed semen is not yet an ideal product, but improvements will continue to be made (Seidel, 2012;Rath et al, 2013). While I have emphasized how sexed semen is produced and used in the United States, the situation is very similar in Canada and several other countries.…”
Section: Sexed Semen 163mentioning
confidence: 99%
“…A published study by Klinc et al (2007) indicated that addition of certain antioxidants to sperm during the sorting process was very beneficial to fertility under European condition, but numbers of inseminations were limited. In any case, fertility of sexed semen likely will continue to improve with further research (Rath et al, 2013). In addition, procedures to optimize timing of AI for sexed semen with ovulation synchronization procedures are being thoroughly researched.…”
Section: Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, other more efficient procedures than flow cytometry are to be developed. With regard to the first target, research is currently done for identification of Y chromosome-specific sequences by bi-functionalised gold nanoparticles and triplex hybridisation in vivo as well as developing a new laser-controlled deflection system that replaces the deflection of spermatozoa in the electrostatic field [44]. In addition, parallel sorting based on microfluidic chips is being tested to avoid the complex orientation of spermatozoa by the flow-tip, therefore providing much higher rates of sorting [42].…”
Section: Daily Use Of Frozen-thawed Semen and Of Sex-sorted Sperm In mentioning
confidence: 99%
“…The demand for livestock products like meat, milk and dairy products have increased globally; to meet this demand, utilization of modern technologies to promote sustainable production of animals assumes paramount importance. Pre -sexed sperm or embryo mediated livestock production along with other genomic, proteomic and phenomics technologies offers a promising breeding strategy to meet the increased demand for food production (Rath et al, 2013). Determination of sex at the earliest stage can reduce the management cost thorough selective management of superior bulls or cows.…”
Section: Introductionmentioning
confidence: 99%